Integrated Green Mining Technology Package for Emission Reduction: A Design Science Approach in an Indonesian Open-Pit Mine - Hendra Sani; Syamsuddin Syamsuddin (Ali Institute of Research and Publication, 2026)
Mine decarbonisation studies still tend to evaluate electrification, energy efficiency, and renewable energy as separate interventions; therefore, evidence on integrated operational deployment remains limited, particularly for medium-scale open-pit mines in developing countries. This study evaluates whether an integrated green mining package can reduce Scope 1 and 2 emissions without undermining day-to-day operational reliability. Using a Design Science Research approach, the study developed and piloted a package consisting of trolley-assist haulage, battery-electric support vehicles, variable speed drives for dewatering pumps, an energy management system, and a solar PV–battery microgrid. Baseline and pilot performance were compared over two three-month periods using fuel logs, electricity meters, telematics, and PV/battery logger data. Emissions were calculated from activity data and IPCC-based emission factors, while renewable integration was assessed using HOMER Pro simulation. Diesel consumption declined from 4,000,000 L to 3,256,000 L (−18.6%), and purchased electricity decreased from 10,000 MWh to 9,060 MWh (−9.4%). The PV system generated 4,050 MWh, supplying about 30.9% of pilot-period electricity demand. Total Scope 1 and 2 emissions fell from 18,920 tCO₂e to 16,155 tCO₂e (−14.6%). The pilot also showed that electrification increased on-site electricity demand, making EMS coordination and renewable supply critical enabling conditions rather than optional add-ons. The novelty of this study lies in field-validating an integrated decarbonisation package instead of a single technology. The findings provide operational-scale evidence for medium-scale mines and support policies on electrification-ready microgrids, performance-based incentives, and standardised Scope 1 and 2 reporting.